2015
DOI: 10.1177/2048872615585518
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of high-sensitivity cardiac troponin T and I differ in patients with ST-segment elevation myocardial infarction treated by primary coronary intervention

Abstract: Kinetics of hs-cTnT, hs-cTnI and s-cTnI differ significantly with a linear decrease regarding both cTnI assays contrasting with a biphasic shape curve for hs-cTnT. This is of importance for clinical management of patients in routine settings especially in follow-up after STEMI including the suspicion of reinfarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
66
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 48 publications
6
66
1
1
Order By: Relevance
“…Furthermore, since cTnI and cTnT are present in the sarcomeric complex in a molecular ratio of 1:1, these differences between the circulating cTns are probably related to differences in intra- [130] or extra-cellular [131][132][133] catabolism and the peripheral turnover of cTnI and cTnT. A recent study [134] found that circulating levels of cTnT, unlike cTnI, have a diurnal rhythm, thus bearing out the hypothesis that there are some differences in the release from cardiomyocytes and/or peripheral turnover between cTnI and cTnT.…”
Section: Do Differences In Troponin-dependent 99th Url Values Depend mentioning
confidence: 99%
“…Furthermore, since cTnI and cTnT are present in the sarcomeric complex in a molecular ratio of 1:1, these differences between the circulating cTns are probably related to differences in intra- [130] or extra-cellular [131][132][133] catabolism and the peripheral turnover of cTnI and cTnT. A recent study [134] found that circulating levels of cTnT, unlike cTnI, have a diurnal rhythm, thus bearing out the hypothesis that there are some differences in the release from cardiomyocytes and/or peripheral turnover between cTnI and cTnT.…”
Section: Do Differences In Troponin-dependent 99th Url Values Depend mentioning
confidence: 99%
“…Heart Fatty Acid Binding Protein (H-FABP), a highly myocardium-specific protein [10] and early rise marker of ACS [11], is a potential candidate. Rising H-FABP is detectable within at least 30 min following the onset of AMI, with concentrations that peak at approximately 6–8 h [12, 13] compared to 10–13 h for hs-cTnI and hs-cTnT [14]. In addition, the recent availability of a commercial immunoturbidimetric assay for H-FABP overcomes issues with previous point of care tests and ELISA-based assays, and means this biomarker can now be measured more reliably using the main laboratory platform [15, 16], concurrently with hs-cTn assays, and generate results within 20 min from blood sampling.…”
Section: Introductionmentioning
confidence: 99%
“…Our team showed that hs-T-troponin follows a specific kinetic characterized by a second peak [14] after STEMI by comparison to hs-TnI. While Troponin was strongly related to infarct size and prognosis after STEMI [15][16][17], the diagnosis performance of the second peak is unclear as regards the MVO determination.…”
Section: Introductionmentioning
confidence: 99%
“…Laugaudin et al [14] showed that the hs-TnT first phase of decay appeared between 24 and 48 h after pPCI, and the second peak (when present) around 72 h post MI. All those 3-time courses of blood test were systematically available in our patients, so as to systematically record a possible 2nd peak of hs-TnT.…”
Section: Limitationsmentioning
confidence: 99%